PENGARUH RENDAMAN KAYU ANGIN (Usnea baileyi) DALAM NIRA SEGAR DAN NIRA REBUS TERHADAP HATI TIKUS (Rattus norvegicus) YANG TERPAPAR TIMBAL ASETAT - Desak Made Malini; Iin Supartinah; Madihah Madihah; Andi Perdana (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2019)
Lead acetate inhaled caused oxidative damage of liver due to the formation of free radicals. Ones of the plant thathas a high antioxidant content is Usnea baileyi. This study aims to examine the potency of fresh and boiled U.baileyi to reducing rats liver damage induced by lead acetate. This study used randomized complete design withnine treatments and three replications. Twenty seven male rats were randomly divided into 9 groups namely onepositive control group (given 100 mg/kb bw lead acetate), two negative control groups (given 1 ml fresh sap and 1ml boiled sap), three groups given U. Baileyi immersion treatment in fresh sap and three group treated U.Baileyi immersion in boiled sap with dose of 3,500 mg/kg BW, 6,000 mg/kg BW and 10,500 mg/kg BW afterinduced by 100 mg/kg BW lead acetate. Treatment was given orally for 15 consecutive days The results showedthat the morphology of rats treated with U. baileyi dosages of 6,000 mg/kg bw and U. baileyi 10,500 mg/kg b wboth in fresh sap and boiled sap had morphology that was not significantly different from negative controls.Whereas in the histological structure only the dose U. baileyi 10,500 mg/kg Bw did not show a significantdifference with negative cotrol. It can be concluded that the dose of U. baileyi 10,500 mg/kg Bw rats in boiled sapgave the best effect in reducing damage to liver histology of rats induced by lead acetate. Key words: lead acetate, liver, sap, Usnea baileyi,